2020
DOI: 10.5658/wood.2020.48.5.641
|View full text |Cite
|
Sign up to set email alerts
|

Termiticidal Activity and Chemical Components of Bamboo Vinegar against Subterranean Termites under Different Pyrolysis Temperatures

Abstract: In this study, the chemical components and termiticidal activities of bamboo vinegar against subterranean termite were evaluated. Bamboo vinegar used in this study were produced from Mayan (Gigantochloa robusta Kurz.), Balcoa (Bambusa balcooa Roxb.), and Taiwan (Dendrocalamus latiflorus Munro). It was analyzed by gravimetric methods. Rubberwood (Hevea brasiliensis) was soaked for 24 h and tested against Coptotermes curvignathus Holmgren according to the Indonesian National Standard (SNI 7207-2014). The bamboo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…4 shows that the greater the concentration, the more termites died. (Arsyad et al, 2020;Oramahi et al, 2022;Suprianto et al, 2023).…”
Section: Mortality Of Subterranean Termitesmentioning
confidence: 99%
“…4 shows that the greater the concentration, the more termites died. (Arsyad et al, 2020;Oramahi et al, 2022;Suprianto et al, 2023).…”
Section: Mortality Of Subterranean Termitesmentioning
confidence: 99%
“…Termites are wood-eating pests (Arinana et al, 2022;Su and Scheffrahn, 2000). Since termites damage wooden buildings, many studies have been conducted to control them in various ways (Adfa et al, 2020(Adfa et al, , 2023Arsyad et al, 2020;Cahyono et al, 2020;Ella Nkogo et al, 2022;Im and Han, 2020;Lee et al, 2020;Oramahi et al, 2022;Priadi et al, 2023). However, they also serve as ecological suppliers providing various nu-trients, including nitrogen compounds (Govorushko, 2019;Lobry de Bruyn and Conacher, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The wood vinegar contains primary chemical components such as acids, ketones, furans, benzene, phenols, sugars, and guaiacols. Arsyad et al (2020) reported that wood vinegar obtained from bamboo pyrolyzed at 400℃ contains phenols and acids that exhibit antitermitic activity.…”
Section: Introductionmentioning
confidence: 99%